Pregnant Women’s Views on the Type of Delivery: Determinants and Relationships - Nooshin Jalali; Shahrzad Hadavand; Farhad Jafari; Maryam Rabiee; Kobra Khajavi Shojaie (Journal of Holistic Nursing and Midwifery)
Introduction: In recent years, the rate of delivery by Cesarean Section (CS) has increased in many countries. Many factors are responsible for this trend which are beyond the clinical practice of gynecologists. Objective: The purpose of this study is to investigate factors related to the preference for delivery type in pregnant women referred to a hospital in Tehran City, Iran. Materials and Methods: This analytical cross-sectional study was conducted on 400 pregnant women referred to one of the hospitals in Tehran, in 2016. A questionnaire for determining the women’s perspective about the factors associated with the choice of delivery mode was used for data collection. It had two parts; the first part surveyed demographic and obstetric characteristics, and the second part evaluated the preference of pregnant women for delivery type. For analyzing data, the Pearson correlation, the Chi-squared test, and t-test were carried out. Results: The Mean±SD age of the participants was 30.43±4.93 years; 65.8% of them were housewives, and 55.2% had a university education. About 63.5% had not participated in any childbirth education classes. The preferred delivery in 59.28% of the participants was a normal delivery. The correlation test results reported a negative correlation between the scores obtained by pregnant women and their preferred delivery mode (P=0.001, r=-0.6). Furthermore, the t-test results showed a significant difference between the two groups (group in favor of normal delivery and the group in favor of Cesarean Section); those with lower scores (negative views towards normal delivery) preferred CS (P<0.001). The Chi-squared test results reported that women’s preference for delivery mode had a significant correlation with their occupation (P=0.042), education (P=0.033), number of children (P=0.001), their first delivery method (P=0.001), and participation in childbirth education classes (P=0.001). In other words, the employed and university student women, those with higher educational level, women with a history of normal delivery and participation in childbirth education classes had a greater tendency toward the normal delivery. Conclusion: The pregnant women’s views on the mode of delivery are related to the choice of delivery mode. Education, training, recommendations of phycision and midwife, Spouse, friends, relatives, and maternity preparation classes are directly related to their choice of delivery mode.